2022
DOI: 10.3390/ijms23126569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Passage Number of Conditioned Medium Collected from Equine Amniotic Fluid Mesenchymal Stem Cells: Porcine Oocyte Maturation and Embryo Development

Abstract: Oocyte in vitro maturation (IVM) is the most important first step in in vitro embryo production. One prerequisite for the success of IVM in oocytes is to provide a rich culture microenvironment that meets the nutritional needs of developing oocytes. We applied different equine amniotic fluid mesenchymal stem cell conditioned medium (eAFMSC-CM) from passages 7, 18, and 27 to porcine oocytes during IVM to determine its effects on oocyte development and subsequent embryo development, specifically. The eAFMSC-CM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…The normal development of early embryos serves as the primary indicator in the assessment of the cytoplasmic maturation of oocytes and is an important criterion for evaluating oocyte quality [33][34][35][36]. Our study demonstrated a significant improvement in the cleavage rates and blastocyst formation rates of embryos that were subjected to subsequent IVF and SCNT following FA supplementation.…”
Section: Discussionmentioning
confidence: 58%
“…The normal development of early embryos serves as the primary indicator in the assessment of the cytoplasmic maturation of oocytes and is an important criterion for evaluating oocyte quality [33][34][35][36]. Our study demonstrated a significant improvement in the cleavage rates and blastocyst formation rates of embryos that were subjected to subsequent IVF and SCNT following FA supplementation.…”
Section: Discussionmentioning
confidence: 58%
“…Cancer cells during the cell metabolism usually excrete various metabolites into the intracellular media. Among them are GSH and other products that may play the role of reducing agents [ 45 , 46 ]. Therefore, when redox-responsive nanoparticles are added to the cancer cell medium, the metabolites can cause some reduction processes in their disulfide sites, and even aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to partial aggregation of the MNP-SS in the intercellular medium containing cell metabolites, some of which can be relatively active reducing agents, such as GSH, cysteine, etc. [ 45 , 46 ]. Tests on the colloidal stability in the conditioned medium showed that the MNP-SS partially aggregates and becomes more polydispersed ( Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…Despite advances in culture conditions, media and protocols for oocyte maturation and embryo development, in vitro outcomes are still far from desirable compared with embryos produced in vivo ( 19 , 20 ). In particular, recent studies have shown the beneficial effect of co-culture with MSCs ( 21 ), oviduct cells, and cumulus cells ( 22 , 23 ) on the development of oocytes and embryos in various mammalian species, including cattle ( 24 ), horses ( 25 ), pigs ( 26 ) and canines ( 27 ). Therefore, culture conditions are crucial in determining the quality of in vitro -produced embryos.…”
Section: Discussionmentioning
confidence: 99%